Why do people migrate? : labour market security and migration decisions - Maciej Duszczyk (2024)
By looking at case studies from around Europe, this book focuses the impact of the expected labour market security on migration decision-making and will prove invaluable for researchers, leaders and policy makers in the field of politics and migration studies.